Propagation and deposition of stony debris flows at channel confluences. Issue 7 (4th July 2015) - Stancanelli, L. M.; Lanzoni, S.; Foti, E.
Abstract The fluid dynamics of stony debris flows generated in two small tributaries adjacent to each other and flowing into a main receiving channel was analyzed experimentally at a laboratory scale. The analysis on the propagation along the tributaries and deposition in the main channel provide information about sediment‐water mobility, dangerous damming, and potential hazard. Debris flows were generated by releasing a preset water discharge over an erodible layer of saturated gravels material. As a consequence, the debris flow sediment concentration varied accordingly to the entrainment rate which, in turn, was strongly controlled by the tributary slope. The data collected by acoustic level sensors, pore fluid pressure transducers, and a load cell were used to characterize the evolution of bulk density and solid concentration of the sediment‐water mixture. These two parameters were relevant to assess the stony debris flow mobility which contributes to determine the shape of sediment deposits in the main channel. The detailed bed topography surveys carried out in the main channel at the end of each experiment provided information on the morphology of these deposits and on the interplay of adjacent confluences. The influences of confluence angle, tributary slopes, and triggering conditions have been investigated, for a total of 18 different configurations. Within the investigated range of parameters, the slope angle was the parameter that mainly influences the stony debris flow mobility while, for adjacent confluences, the degree of obstruction within the receiving channel was strongly influenced by the triggering scenario.